Assessing the impact: Environmental impact assessment in the textile and garment sector in Bangladesh, Cambodia, Indonesia and Viet Nam - Samantha Sharpe; Monique Retamal; M. Cristina Martinez-Fernandez (International Labour Organization (ILO), 2022)
Environmental regulations provide protection for both environmental assets and the livelihoods of communities that depend on these assets. The analysis evaluates the Environmental Impact Assessment (EIA) processes for proponents of industrial projects in Bangladesh, Cambodia, Indonesia and Viet Nam. The paper finds that enhanced environmental outcomes can be achieved by greater awareness among proponents of the links between environmental management (as facilitated by the EIA process) and sustainable development.
Keywords: 330; green jobs; sustainable development; clothing and textile industries; partnerships